CAPITAL STRUCTURE AND VALUE CREATION IN THE NIGERIAN BANKING INDUSTRY - Abina, Isilamiyat Esther (Journal of Healthcare Management and Administration (JHMA), 2022)
This study examines the relationship between capital structure and firm performance in the banking sector of the Nigerian economy. Capital structure, which refers to the composition of debt and equity in a firm's funding sources, has been a topic of debate in finance literature. Various theories, including the Agency Cost Theory, Pecking Order Theory, and Static Trade-Off Theory, attempt to explain this relationship. However, empirical studies conducted thus far have yielded inconclusive results and are predominantly based on developed countries, with limited focus on developing countries, particularly in Africa. The objective of this study is to fill this gap by investigating the capital structure and firm performance of quoted Nigerian banks. The study aims to determine the impact of the debt-equity mix on the performance and value of these banks. The wealth of shareholders, represented by the product of the company's market price and total outstanding shares, is used as a measure of firm value. The study also considers sectoral considerations, such as the specific characteristics of the banking sector, which may influence the capital structure-performance relationship. To achieve the research objective, rigorous empirical analysis will be conducted using data from banks listed on the Nigeria Stock Exchange. The study will adopt sophisticated analytical techniques to overcome the limitations observed in previous studies, which often employed inappropriate methodologies. By examining the experiences of banks in a developing country context, this research aims to provide fresh insights and answers to the ongoing debates regarding capital structure and firm performance. The findings of this study are expected to contribute to the existing body of knowledge on capital structure and firm performance, particularly in the banking sector. The results will have practical implications for Nigerian banks, policymakers, and investors, as they will provide guidance on the optimal debt-equity mix that can enhance the performance and value of these banks. Additionally, the study will shed light on the factors that contribute to the long-term viability and sustainability of banks, emphasizing the importance of maintaining a quality and sound capital structure.